2010
DOI: 10.1002/hep.23683
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of fatigue in primary biliary cirrhosis: Evaluation of a large clinic practice

Abstract: Quality of life is an important concern for patients with chronic liver disease. We sought to describe the frequency, severity, and associations of fatigue, in patients with primary biliary cirrhosis (PBC). We performed association testing between PBC-40 multidomain disease-specific quality of life responses and clinical findings. Three hundred twenty-seven patients from a single clinic with PBC (94% female, 92% AMA-positive) were evaluated. The average age was 57 years and average disease duration 7.2 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 32 publications
2
37
1
2
Order By: Relevance
“…Taken together, these findings suggest that, whereas fatigue is a highly significant Control values are for an age-and sex-matched control population not preselected for symptom severity who completed a version of the PBC-40 (the PBC-40c) which was validated for completion by non-PBC patients for the purposes of this study and which was found to demonstrate construct validity (Supporting Table 1). In addition to the potentially generic symptom domains demonstrated in this figure, the impact of pruritus and general PBC symptoms was unsurprisingly greater in PBC patients than in matched controls (pruritus: PBC-40 pruritus domain score median 4 [interquartile range 0-9 in PBC patients versus 2 [0-3] in controls, P < 0.0001; general PBC symptoms 16 [12][13][14][15][16][17][18][19][20] versus 10 [8-13], P < 0.0001). Dotted lines for each symptom domain represent the cutoff for clinically significant symptoms (defined as mean value for normal subjects 12 SD).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Taken together, these findings suggest that, whereas fatigue is a highly significant Control values are for an age-and sex-matched control population not preselected for symptom severity who completed a version of the PBC-40 (the PBC-40c) which was validated for completion by non-PBC patients for the purposes of this study and which was found to demonstrate construct validity (Supporting Table 1). In addition to the potentially generic symptom domains demonstrated in this figure, the impact of pruritus and general PBC symptoms was unsurprisingly greater in PBC patients than in matched controls (pruritus: PBC-40 pruritus domain score median 4 [interquartile range 0-9 in PBC patients versus 2 [0-3] in controls, P < 0.0001; general PBC symptoms 16 [12][13][14][15][16][17][18][19][20] versus 10 [8-13], P < 0.0001). Dotted lines for each symptom domain represent the cutoff for clinically significant symptoms (defined as mean value for normal subjects 12 SD).…”
Section: Resultsmentioning
confidence: 85%
“…Given the previous controversy regarding the impact of depression in the expression of fatigue in PBC, 12,22 we explored the interrelationship between fatigue severity and depression (defined by HADS-D 11 indicating "caseness" for depression). Although a correlation was seen between fatigue severity and HADS-D score (r 2 5 0.49, P < 0.0001) the interrelation between depression and fatigue was complex, involving other symptom sets (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stwierdzono w nim, że spośród 48% osób skarżących się na zespół przewlekłego zmęczenia aż 44% uznało je w badaniu kwestionariuszowym za objaw o natężeniu co najmniej średnim, ale co istotne -takie nasilenie zespołu przewlekłego zmęczenia podało także 25% badanych, którzy wcześniej nie zgłaszali tej dolegliwości. Pozytywnie z przewlekłym zmęczeniem korelowały wskaźnik masy ciała, świąd skóry, suchość błon śluzo-wych, fibromialgia i sklerodermia [9].…”
Section: Częstość Występowania Zespołu Przewlekłego Zmęczenia W Pierwunclassified